Inhibition of Partially Purified Sorbitol Dehydrogenase Activity From Sera of Patients With Type I Diabetes - Nashwan I. Abo (College of Education for Pure Sciences, 2010)
Abstract In this research Sorbitol dehydrogenase (SDH) was partially purified from sera of patients with type I diabetes mellitus by dialysis and ion exchange chromatography step by step. One peak of SDH activity was obtained with specific activity of 40.065 unit/mg protein and with purification fold of 98.9 compared to crud enzyme. Inhibition of SDH was studied by Glibenclamide and Rosiglitazone drugs, the best concentration of both inhibiters was 6mM. The mechanism of SDH inhibition by using both drugs were noncompetitive. There is no change in Km value 100 mM. Vmax value without inhibitor was 22.175 but 13.634 and 14.615 unit/ml with Glibenclamide and Rosiglitazone respectively. Accordingly, the inhibition constant Ki was calculated and appeared 7mM for both inhibitors above. Finally, we propose that action of these drugs may contribute to decrease patients with type I diabetes complications through inhibition SDH which plays an important role in polyol pathway.